Oral health promotion practices of Australian community mental health professionals: a cross sectional web-based survey - Roisin McGrath; Rodrigo Marino; Julie Satur (BMC, 2021)
Abstract Background This study explored the oral health promotion practices of Australian community mental health professionals working with people living with severe mental illness (SMI). Methods An anonymous cross-sectional web-based survey was distributed to all Community Rehabilitation and Support Workers (CRSWs) working at Neami National (n = 471), an Australian community mental health service. The validated questionnaire assessed participants' self-rated oral health knowledge and confidence (7 questions); their perceived barriers (9 questions) and attitudes (5 questions) to oral health promotion; and their oral health promotion practices (7 questions). Differences in responses between groups were analysed using Chi-square, Fisher's exact and Mann-Whitney U tests. Logistic Regression Analysis served to explore the probability of providing oral health support to mental health consumers. Results A total of 141 CRSWs were included in this study, achieving a response rate of 30 percent. Roughly two-fifths (39.0%) of participants had oral health training in the previous 12-months. The majority of CRSWs (89.3%) believed ('Agreed' or 'Strongly agreed') that mental health support workers have a role to play in promoting oral health. However, less than half (44.0%) of CRSWs practiced oral health promotion activities when working with mental health consumers. When asked about barriers to promoting oral health, 'lack of consumer interest' was the most prevalent issue. CRSWs who had oral health training were over three-times (OR 3.5, 95% CI 1.25-9.83, p = 0.017) more likely to provide oral health support. Results showed the provision of oral health support was most strongly associated with self-rated knowledge and confidence (OR 4.089, 95% CI 1.629-10.263, p = 0.003) and attitudes to oral health promotion (OR 3.906, 95% CI 1.77-8.65, p = 0.001). Conclusion The results of this study suggest that mental health support workers who have more positive attitudes to oral health promotion and who have higher self-rated oral health knowledge and confidence are more likely to provide oral health support in their professional role. Training for community mental health professionals is essential to build confidence and skills to promote oral health for mental health consumers.